Police sexual coercion and its association with risky sex work and substance use behaviors among female sex workers in St. Petersburg and Orenburg, Russia - Odinokova, Veronika (2013)
BACKGROUND: Extensive research documents that female sex workers (FSWs) in Russia are very vulnerable to abuses from police, including police sexual coercion. However, despite qualitative data suggesting abusive policing practices are more likely for FSWs contending with substance abuse issues and risky sex work contexts, there is a paucity of quantitative study evaluating these associations specifically in terms of police sexual coercion. Such research is needed to guide structural interventions to improve health and safety for FSWs in Russia and globally. OBJECTIVE: The purpose of this study is to assess the prevalence of police sexual coercion among FSWs from two Russian cities, St. Petersburg and Orenburg, and to determine whether riskier sex work behaviors and contexts and substance use behaviors, including both IDU and risky alcohol use, are associated with increased risk for sexual coercion from police METHOD: FSWs in St. Petersburg and Orenburg were recruited via time-location and convenience sampling and completed structured surveys on demographics (age, education), sex work risks (e.g., violence during sex work) and substance use. Logistic regression analyses assessed associations of substance use and risky sex work with police sexual coercion, adjusting for demographics. RESULTS: Participants (N=896) were aged 15 and older (94% were 20+ years). Most (69%) reported past year binge alcohol use, and 48% reported IDU the day before. Half (56%) reported 4+ clients per day. Rape during sex work ever was reported by 64%. Police sexual coercion in the past 12 months was reported by 38%. In the multivariate model, both current IDU (AOR=2.09, CI=1.45–3.02) and past year binge alcohol use (AOR=1.46, CI=1.03–2.07) were associated with police sexual coercion, as was selling sex on the street (not in venues) (AOR=7.81, CI=4.53–13.48) and rape during sex work (AOR=2.04, CI=1.43–2.92). CONCLUSION: Current findings document the substantial role police sexual violence plays in the lives of FSWs in Russia. These findings also highlight heightened vulnerability to such violence among self-managed and substance abusing FSWs in this context. Structural interventions addressing police violence against FSWs may be useful to improve the health and safety of this population.